N-doped porous carbon nanosheets as pH-universal ORR electrocatalyst in various fuel cell devices. (July 2018) - Liu, Liangzhen; Zeng, Guang; Chen, Junxiang; Bi, Linlin; Dai, Liming; Wen, Zhenhai
Abstract: Exploring high-activity electrocatalyst for oxygen reduction reaction (ORR) is of great significance for a variety of renewable energy conversion and storage technologies. Herein, we report a template-free, economic and environment-friendly strategy for scalable synthesis of N-doped hierarchical porous carbon nanosheets (N-HPCNSs) with biomass water lettuces as carbon precursor. The N-HPCNSs were demonstrated to possess three dimensional (3D) hierarchical porous structures with a high surface area and uniform N-doping. Systematic electrochemical study revealed that the N-HPCNSs not only hold numerous active sites but also manifest high intrinsic activity for each of the active sites toward ORR in pH-universal electrolyte of alkali, acid and neutral. With the N-HPCNSs as cathode electrocatalyst, three types of home-made fuel cells were set up that run in alkaline, acidic and neutral medium, i.e., Zn-air alkaline fuel cell, direct methanol fuel cell, and microbial fuel cell, respectively, further demonstrating its potential to replace the high-cost Pt-based electrocatalysts for practical applications. Owning to the multiple attracting features, including high catalytic activity, good durability, low cost, and scalable production, the as-developed pH-universal N-HPCNS electrocatalysts may open a promising avenue for developing the next-generation cathode electrocatalysts for fuel cells of practical significance. Graphical abstract: N-doped porous carbon nanosheets possess three dimensional (3D) hierarchical porous structures with a high surface area were prepared as high-activity ORR electrocatalysts in pH-universal electrolyte, three types of home-made fuel cells running in alkaline, acidic and neutral medium, i.e., Zn-air fuel cell, direct methanol fuel cell, and microbial fuel cell, were set up and show decent performance, demonstrating its potential to replace the high-cost Pt-based electrocatalysts for practical applications.fx1 Highlights: Porous carbon nanosheets with three dimensional hierarchical porous structures and high surface area. Numerous active sites and high intrinsic activity for electrocatalysis of oxygen reduction. High catalytic activity, good durability, low cost, and scalable production. Cathode electrocatalysts for fuel cell working in pH-universal electrolyte.